INDICATORS OF INSULIN RESISTANCE AND ADIPOKINES LEVELS IN WOMEN WITH NORMAL PREGNANCY, DELIVERY SURGICALLY - A. V. Shestopalov; Y. A. Miroshnichenko; A. N. Rymashevsky (Кубанский научный медицинский вестник)
This article presents the results of a survey of 40 women with physiological pregnancy cesarean delivery at the age of 21-40 years and 12 non-pregnant women. The level of content of adiponectin, resistin, insulin and glucose levels in the blood plasma by ELISA. Calculated BMI and HOMA-IR. The study found that multiparous women develop more severe insulin resistance, characterized by increasing levels of insulin, glucose, HOMA-IR compared with nulliparous. However, pregnancy is characterized by physiological changes in endocrine activity of adipose tissue, expressed in decreased level of adiponectin and resistin concentration is increased.